Nilai-nilai Pendidikan dalam Upacara Adat Mangupa dan Relevansinya terhadap Penguatan Profil Pelajar Pancasila - Annisa Nabila; Dini Aisyah Nur; Laila Sakinah; Yenni Efrida Lubis; Rahmi Wahyuni (PT. Willy Print Art, 2025)
The Mangupa ceremony is one of the most significant traditional rituals of the Mandailing community, rich in educational, moral, and spiritual values. This study aims to examine the educational values embedded in the Mangupa ceremony and their relevance to strengthening the Pancasila Student Profile within the context of character education. This research employs a qualitative descriptive approach through literature studies and analysis of cultural values reflected in the symbols, meanings, and rituals of the ceremony. The findings reveal that the Mangupa ceremony embodies several core educational values, including religious devotion and gratitude, respect for parents and tradition, independence and responsibility, love for nature and ecological awareness, as well as solidarity and mutual cooperation. These values represent moral and social principles that can shape students to become faithful, virtuous, independent, cooperative, critical-thinking, and globally minded individuals in accordance with the dimensions of the Pancasila Student Profile. The Mangupa tradition thus functions not only as a cultural ritual but also as an educational medium that instills spiritual, social, and ecological awareness. Therefore, preserving and integrating the values contained in the Mangupa ceremony into character education based on local wisdom is highly relevant to strengthening the cultural identity and moral integrity of Indonesia’s young generation.